Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1088/0960-1317/19/10/105010
|View full text |Cite
|
Sign up to set email alerts
|

Microfabrication on a curved surface using 3D microlens array projection

Abstract: Accurate three-dimensional microstructures on silicon or other substrates are becoming increasingly important for optical, electronic, biomedical and medical applications. Traditional microfabrication processes based on cleanroom lithography and dry or wet etching processes are essentially two-dimensional methods. In the past, complicated procedures were designed to create some three-dimensional microstructures; however, these processes were mainly used to create features on planar silicon wafer substrates usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…Ultraprecision machining was also applied to fabricate 3D compound eye lens arrays [63,64]. It was reported that 601 individual compound eye microlenses (aperture of 0.58 mm) and the related microprisms were produced in a 20 mm diameter area, providing a large light deviation angle of 18.43° and maximal FOV of 180°, if the entire hemispherical surface is fabricated with microlenses.…”
Section: Ultraprecision Machining Methodsmentioning
confidence: 99%
“…Ultraprecision machining was also applied to fabricate 3D compound eye lens arrays [63,64]. It was reported that 601 individual compound eye microlenses (aperture of 0.58 mm) and the related microprisms were produced in a 20 mm diameter area, providing a large light deviation angle of 18.43° and maximal FOV of 180°, if the entire hemispherical surface is fabricated with microlenses.…”
Section: Ultraprecision Machining Methodsmentioning
confidence: 99%
“…Various methods for the fabrication of curved microlens array have been developed, including, but not limited to, reflow process, 4 laser direct-write, 5,6 3D microlens array projection 7 and soft lithography. 8 Most of these methods are processed on a curved substrate or by deforming the planar microlens array on elastomeric membrane into curved microlens array.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most of these methods are processed on a curved substrate or by deforming the planar microlens array on elastomeric membrane into curved microlens array. 9 The fabrication methods processed on a curved substrate such as direct writing, [10][11][12] which employ a focused laser beam or an electron beam with a quasi continuous intensity modulation, have a long production cycle and high production costs. Although the fabrication deforming a planar microlens array is flexible, the complex process and harsh control condition may restrict its development.…”
Section: Introductionmentioning
confidence: 99%
“…Toric and progressive addition lenses (PAL) are a kind of opthalmic lenses with freeform surface, and their application is limited for a long time by the difficulty to design and manufacture. At present, freeform surfaces can be machined by fast tool servo [1][2][3][4], micro-milling [5][6][7], fly-cutting or raster milling [8,9], and slow tool servo (STS) [10][11][12][13][14] etc. Among these technologies, with the advantages of high surface accuracy and high machining efficiency, STS is gradually applied to machine freeform surface.…”
Section: Introductionmentioning
confidence: 99%
“…One of such improvements can be made to STS turning by developing predictive models for surface roughness. There were a few papers discussing fabrication of freeform surface using STS [10][11][12][13][14], and path planning and error compensation [10,15,16] were also reported. However, little literature dealt with the prediction of surface topography using STS.…”
Section: Introductionmentioning
confidence: 99%